1984
DOI: 10.1111/j.1600-0722.1984.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus (HPV) antigens and local immunologic reactivity in oral squamous cell tumors and hyperplasias

Abstract: – A series of 191 oral mucosal tumors including those with suspected HPV (Human Papilloma Virus) etiology; squamous cell papilloma (SQP), condyloma acuminatum (CA), focal epithelial hyperplasia (FEH), as well as those regarded as unrelated to HPV; fibrous hyperplasia (FH), papillary hyperplasia (PH), and true fibroma (TF), were analyzed for HPV structural proteins (by indirect immunoperoxidase IP‐PAP technique), for the presence of epithelial dysplasia, and for the cellular composition (B and T lymphocytes, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…Jenson et al [38] were the first to report, in 1982, that 2/5 oral SCPs expressed HPV common structural antigens. We confirmed these results by reporting initially, in 1983 [71], 5 HPV-positive papillomas among 9 lesions, and subsequently 40 papillomas, of which 41% stained positively for HPV antigens [72]. The largest series analyzed so far is published by Padayachee and van Wyk [51], who found HPV antigens in 41% of the analyzed 140 samples.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Jenson et al [38] were the first to report, in 1982, that 2/5 oral SCPs expressed HPV common structural antigens. We confirmed these results by reporting initially, in 1983 [71], 5 HPV-positive papillomas among 9 lesions, and subsequently 40 papillomas, of which 41% stained positively for HPV antigens [72]. The largest series analyzed so far is published by Padayachee and van Wyk [51], who found HPV antigens in 41% of the analyzed 140 samples.…”
Section: Introductionsupporting
confidence: 69%
“…As early as 1982, Lutzner et al [44] reported the presence of HPV type 2a in one verruca by Southern blot hybridization. Subsequently, immunohistochemistry was used to verify the expression of HPV antigens in oral warts, and HPV detection rates from 45% to 100% have been reported [38,39,47,70,72]. In 1986 Adler-Storthz et al [3] identified HPV types 2 and 4 in 6/11 oral verrucas.…”
Section: Evidence For Hpv Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…p53 expression was inversely cor- infections in uterine cervical lesions, their prevalence in oral lesions is highly variable, e.g. 0-78% for oral SCC [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . This variability may stem from differences in the methods used to detect HPV-DNA such as PCR, Southern blot hybridization and in situ hybridization (ISH).…”
Section: Introductionmentioning
confidence: 99%